Molecular Approaches For Identification, Characterisation And Quantification Of Probiotic Lactobacillus Strains For Poultry - Lee, Chin Mei (2009)

(untitled)
The use of probiotics as an alternative to antibiotic growth promoter has gained popularity in the commercial poultry industry in view of the hazards posed by antibiotics to human and animal health. However, the science behind the probiotic microorganisms has been poor with respect to their identity at the species and strain level, their interaction with the host animal, and their efficacy in poultry practices. Thus, a reliable and efficient method is essential to monitor the probiotic microorganisms and to perform quality control of commercial probiotic products. In the present study, molecular methods were applied for reidentification, characterisation and enumeration of 12 probiotic Lactobacillus strains which were previously identified with classical biochemical tests. Based on comparative sequence analyses of the 16S ribosomal RNA (rRNA) gene and 16S-23S rRNA gene intergenic spacer region (ISR), discrepancies were found in the identification of nine out of the 12 Lactobacillus strains, namely, L. brevis C 1, L. brevis C 10, L. fermentum C 16, L. brevis C 17, L. crispatus I12, L. acidophilus I 16, L. fermentum I 24, L. fermentum I 25 and L. acidophilus I 26. These strains were reidentified as L. reuteri C 1, L. reuteri C 10, L. reuteri C 16, L. panis C 17, L. brevis I 12, L. gallinarum I 16, L. salivarius I 24, L. brevis I 25 and L. gallinarum I 26. The rate of misidentification is high when conventional identification methods are used.